IMPROVEMENT EFFORTS OF PATROL UNIT OF SAMAPTA UNIT PERFORMANCE IN PREVENTING BURGLARY WITHIN JURISDICTION OF BOYOLALI RESORT POLICE - MARIA OLIVIA RURUPADANG (Indonesian Journal of Police Studies, 2022)
ABSTRACT IMPROVEMENT EFFORTS OF PATROL UNIT OF SAMAPTA UNIT PERFORMANCE IN PREVENTING BURGLARY WITHIN JURISDICTION OF BOYOLALI RESORT POLICE The high rate of burglary in Boyolali certainly related with the lack of maximized patrol implementation. The purposes of the research are to describe the patrol implementation of Samapta Police Unit of Boyolali Resort Police, to determine factors to affect the performance of Patrol Unit of Samapta Unit of Boyolali Resort Police, and to determine efforts to improve the performance of Patrol Unit in order to prevent the burglary crime. Theories and concepts used for the research are in accordance with the research title i.e. concepts of effort, improvement, Samapta Police Unit, patrol, burglary; as well as theories of management and performance. The research uses qualitative approach and descriptive analysis research method. The data used for this research are sourced from both primary data sources in the form of interview results with various interviewees, and secondary data sources in the form of books and documents related to the research. The technique of data analysis used comprises data reduction, data presentation, and drawing the conclusion. The validation of data used in the research is through triangulation towards the sources, techniques, and the time of data The research findings shows the patrol implementation of Samapta Unit of Boyolali Resort Police has been through three phases in accordance with the procedure, i.e. preparation, implementation, and closure phases. However, the implementation has not been maximized due to the patrol implementation has not reached the whole area of Boyolali Regency, as well as the high rate of the burglary itself. The inhibiting factors of patrol implementation by Boyolali Resort Police include the lack of patrol unit personnel, budget, facilities, as well as the lack of positive response and active participation from the civil society. The improvement efforts that have been done are forming the special teams for night patrols, carrying out circular patrol for the effectiveness and efficiency of work, and involving personnel from another sub-unit in the patrol activities. The suggestion given by the researcher are to maximize the cooperation with the community leaders and Bhabinkamtibnas as the duty executor which are directly adjacent to community, to receive information update regarding communal security. Keywords: Kamtibmas, patrol, performance improvement, Samapta, effort.